Screening for disability in the inner city. Issue 1 (March 1981) - Patrick, D L; Darby, S C; Green, S; Horton, G; Locker, D; Wiggins, R D
Abstract : A 10% sample of private households on the electoral register of the London borough of Lambeth was screened for disable persons aged 16 and over, using a postal questionnaire. After three mailings and individual follow-up of non-responders, 87% of the sample households returned questionnaires. Disability was defined in the screening questionnaire as functional limitations or activity restrictions consequent upon disease or impairment. The overall point prevalence of disability was estimated at 15.4% and the most frequently reported impairments were those of the sense organs, bones, central nervous, circulatory, and respiratory systems. Hearing difficulties were the single most frequently reported functional limitation. A log-linear modelling procedure identified age, marital status, and working status as the factors most strongly associated with disability for both men and women. In addition, men aged 50-64 and not working, and men in manual occupations and living alone, were more likely to report disability. These findings indicate that some population groups are disable by functional limitations and activity restrictions not included in office criteria of identification and assessment. These criteria might be broadened, and serves planned for those population groups with higher rates of reported disability.